PEMIMPIN BERKUALITAS YANG DI TERAPKAN KEPALA REGU PENGAMANAN GUNA MENGHADAPI KOMPLEKSNYA PERMASALAHAN DI LAPAS - Martial Tedi Marlissa; Mitro Subroto (Jurnal Komunikasi Hukum, 2022)
Problems are a natural thing and often occur in life, both in small and large scope, both from personal, family, and within the organization. One example is Correctional Institution (LAPAS) where the problems that arise are more complex because they are related to humans who have temporarily lost their independence so that they require policies and solutions to every problems that occurs so as not to create new problems. For this reason, a quality leader is needed who can build and make LAPAS not only as an institution that fosters convicts, but at the same time as an institution that provides protection and respects the rights of convicts as human beings.